Carbon-neutral architectural design - La Roche, Pablo, 1961- (Boca Raton : CRC Press, 2017)
"The energy used to operate buildings is one of the most significant sources of greenhouse gas emissions. While it is possible to reduce emissions through climate-responsive design, many architects are not trained to do this. Filling an urgent need for a design reference in this emerging field, this book describes how to reduce building-related greenhouse gas emissions through appropriate design techniques. It presents strategies to achieve CO2 reductions, with an emphasis on control of energy flows through the building envelope and passive heating and cooling strategies. This new, revised edition is updated throughout, and includes a new chapter on building simulations."--Provided by publisher.
2.1.2 Computer-Aided Architectural Design Process 2.2 Carbon-Neutral Architectural Design Process ; 2.3 Urban and Neighborhood Scale ; 2.4 Building Scale ; 2.4.1 Operation and Energy ; 2.4.2 Construction ; 2.4.3 Water ; 2.4.4 Waste.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable architecture; Architectural design; Carbon dioxide mitigation; ARCHITECTURE -- Adaptive Reuse & Renovation; ARCHITECTURE -- Buildings -- Landmarks & Monuments; ARCHITECTURE -- Professional Practice; ARCHITECTURE -- Reference; NATURE / Environmental Conservation & Protection; TECHNOLOGY / Construction / General; TECHNOLOGY / Engineering / Civil